Análise do Plano Municipal de Gerenciamento Integrado de Resíduos Sólidos de Ourinhos/SP à luz da Política Nacional de Resíduos Sólidos – Lei 12.305/10 - Coletti, Guilherme Luis (Universidade Federal de São Carlos, 2015)
The great dilemma involving solid waste is related to the increase of its generation as well as with the adequate management of its collection, transportation, processing and final disposal, in such a way as to minimize related environmental and urban impacts. Such dilemma has been consuming high levels of human, technological and financial resources, granting the wastes a significant role in the urban sanitation systems. Thus, Brazil has created, by means of Law 12,305, dated as of August 2nd, 2010, the National Policy of Solid Wastes (PNRS) pursuing the systematization of the waste management in the country holding liable all the parties involved in the life cycle of goods. Among the duties contained therein, the PNRS requires the City Halls to prepare a Municipal Plan for Integrated Management of Solid Wastes, which shall present the minimum content to be implemented in this regard. In this way, this paperwork has the purpose to review the Municipal Plan for Integrated Management of Solid Wastes of the City Ourinhos/SP (PGIRSO) in light of the requirements made by the PNRS and to compare the propositions of such plan with the actions so far taken by the City Hall of Ourinhos/SP. It is concluded that, although the PGIRSO provides the minimum content to implement improvements in the wastes management, it has not been put into force, turning it into a simple bureaucracy with no enforcement related to the social environmental quality of the municipality.
Keywords: Resíduos sólidos; Política Nacional de Resíduos Sólidos (Brasil); Gestão de resíduos sólidos; Ourinhos (SP); Domestic Solid Wastes; Solid Wastes Management; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::METODOS E TECNICAS DO PLANEJAMENTO URBANO E REGIONAL::TECNICAS DE PLANEJAMENTO E PROJETO URBANOS E REGIONAIS